2011
DOI: 10.1007/s12028-011-9528-5
|View full text |Cite
|
Sign up to set email alerts
|

A Clinical Description of Extubation Failure in Patients with Primary Brain Injury

Abstract: The extubation failure rate in our neurocritical care unit is low. In patients with encephalopathy and primary brain injury who were reintubated, respiratory distress caused by altered mental status was the most common cause of reintubation. These patients demonstrated signs disrupted ventilation usually with periods of prolonged hypoventilation. Increased work of breathing from lung injury due to pneumonia or aspiration was not the most common cause of reintubation in this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
25
1
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(39 citation statements)
references
References 26 publications
6
25
1
7
Order By: Relevance
“…We also found a significant number of patients (3.8 %) who required reintubation beyond the 72 h, a cutoff traditionally used to define extubation failure. This is similar to findings of Karanjia et al [26].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We also found a significant number of patients (3.8 %) who required reintubation beyond the 72 h, a cutoff traditionally used to define extubation failure. This is similar to findings of Karanjia et al [26].…”
Section: Discussionsupporting
confidence: 93%
“…Because of the different definitions of extubation failure across studies, it can be difficult to compare the reported incidences of extubation failure. In addition, this variation can be partially explained by the heterogeneity of the studied populations [25,26]. We also found a significant number of patients (3.8 %) who required reintubation beyond the 72 h, a cutoff traditionally used to define extubation failure.…”
Section: Discussionmentioning
confidence: 73%
“…Early extubation allows detection of postoperative neurological complications but may increase the risk of extubation failure. [1][2][3] Delayed extubation has been advocated in high-risk patients, to limit postoperative stress and avoid serious complications such as intracranial haematoma, 4,5 but is associated with increases in pneumonia incidence, morbidity, mortality, tracheotomy, length of stay (LOS) in the intensive care unit (ICU), and hospitalization costs. 6 The timing of extubation after intracranial surgery is usually a combined decision, made by the anaesthetist and the neurosurgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Brain-injured patients may "wean off" positive pressure ventilation without difficulty, but they may continue to require an artificial airway secondary to poor mental status or brain stem and/or lower cranial nerve deficits. The reasons for failed extubation in this population remain poorly understood [16,17]. Counterintuitively, a low score on Glasgow Coma scale (GCS) has not been consistently linked with extubation failure and the need for an artificial airway.…”
Section: Special Considerations For Patients With Brain Injurymentioning
confidence: 99%